Antiquity and Enlightenment culture : new approaches and perspectives - Johnston, Alexandre; Loughlin, Felicity (Metaforms, 2020)
"This volume represents the first move towards a comprehensive overview of the place of antiquity in Enlightenment Europe. Eschewing a narrow focus on any one theme, it seeks to understand eighteenth-century engagements with antiquity on their own terms, focusing on the contexts, questions, and agendas that led people to turn to the ancient past. The contributors show that a profound interest in antiquity permeated all spheres of intellectual and creative endeavour, from antiquarianism to political discourse, travel writing to portraiture, theology to education. They offer new perspectives on familiar figures, such as Rousseau and Hume, as well as insights into hitherto obscure antiquarians and scholars. What emerges is a richer, more textured understanding of the substantial eighteenth-century engagement with antiquity. Contributors are: Anthony Ossa-Richardson, Maria Giulia Franzoni, Thomas Hopkinson, Maeve O'Dwyer, Miriam Al Jamil, Kelsey Jackson Williams, Alan Montgomery, Marta Dieli, Tim Stuart-Buttle, Flora Champy".